The COVID-19 Impact on Online Education – Opportunities and Challenges in a SWOT Analysis - Saraiva, Ana Cristina; Silva, Nuno Alves (International Journal of Research in E-learning, 2021)
The outcomes of the COVID-19 pandemic are having an impact on all areas, with the educational sector being one of the most impacted sectors to be taken into account. The purpose of this article is to identify the main opportunities and challenges of online education as a result of the COVID-19 pandemic, through a selective bibliography providing advice on information sources, and databases. The research methodology was achieved by performing a systematic literature review of what exists on subject, in order to retrieve the main categories for a SWOT analysis, from the points of view of teachers, students and the parents themselves. Finally, it attempts to cover the main contributors to the study domain. For each weakness and challenge, teachers and students can create an opportunity in online learning. The authors also have seen that this type of education is providing a great environment for learning innovation and to face-to-face teaching.